Companies’ choices pivotal under new quarterly reporting regime - WANG, Jiwei (Institutional Knowledge at Singapore Management University, 2024)
A newspaper article reflecting the evidence collected in the report Study on the Risk-based Quarterly Report Regime, which aims to assess the impact of SGX's new regime of releasing most companies from mandatory quarterly reporting on companies and the market.